Analysis of the advantages and disadvantages of the implementation of Fracking in the exploitation of oil and gas in Magdalena Medio in Colombia, from 2012 to 2018 (2019)
This essay aimed to analyse the advantages and disadvantages of the implementation of Fracking in the oiland Gas exploitation in the Magdalena Medio in Colombia, from 2012 to 2018. With the analysis carried out on scientific, medical, journalistic and published articles, which indicate that fracking represents an important threat to air, water, health, public safety, seismic stability and Climate and short- termeconomic income, recurrent problems and damages that cannot be avoided by means of regulatory frameworks, give the theoretical support to make a decision around the subject. The study proposes not to apply this technique in the Magdalena Medio Colombiano, considering the negative impacts to the environment identified by the international community, including the contamination of surface water and Underground, soil contamination, atmospheric, earthquake generation, possible damage to workers’ health by having contact with gases such as methane, among others, and the economic benefits would greatly benefit the Oil and very little would stay in the country.